1993
DOI: 10.1080/00380768.1993.10419179
|View full text |Cite
|
Sign up to set email alerts
|

Kate of oxalate biosynthesis from glycolate and ascorbic acid in spinach leaves

Abstract: The contribution of glycolate as a precursor of oxalate in newly expanding spinach leaves was compared with that of L-ascorbic acid (ASA). Detached spinach leaves were fed with [2-14C]glycolate and [1-1~C]ASA. Using the values of the rate of photorespiratory glycolate synthesis and the incorporation of glycolate-~C into oxalate, the rate of oxalate biosynthesis via glycolate amounted to 34 ~g g-1 fr wt h -1 under light conditions. When the values of incorporation of ASA-14C into oxalate and the turnover rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 13 publications
(11 reference statements)
3
16
0
Order By: Relevance
“…Oxalate salts accumulate in various species of higher plants, such as spinach (Goh and Vityakon 1989;Prokakis and Gonzalez 1990;Kameno et al 1991;Kleczkowski et al 1991;Fujii et al 1993;Takebe et al 1995a,b;Watanabe et al 1995), begonia (Sasaki 1963), Phaseolus vulgaris (Zindler-Frank et al 1989; Barnabas and Arnott 1991), plum and cherry (Sanchez-Alonso and Lachica 1988), and rice seedlings (Ivanov et al 1991). Oxalic acid has been considered to be a by-product of plant metabolism.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Oxalate salts accumulate in various species of higher plants, such as spinach (Goh and Vityakon 1989;Prokakis and Gonzalez 1990;Kameno et al 1991;Kleczkowski et al 1991;Fujii et al 1993;Takebe et al 1995a,b;Watanabe et al 1995), begonia (Sasaki 1963), Phaseolus vulgaris (Zindler-Frank et al 1989; Barnabas and Arnott 1991), plum and cherry (Sanchez-Alonso and Lachica 1988), and rice seedlings (Ivanov et al 1991). Oxalic acid has been considered to be a by-product of plant metabolism.…”
mentioning
confidence: 96%
“…Oxalic acid has been considered to be a by-product of plant metabolism. Fujii et al (1993) suggested that oxalate biosynthesis in spinach leaves is related to photorespiration and that glycolate was an important precursor of oxalate. Furthermore, the rate of oxalate synthesis via glycolate depends on the age of the leaves (Fujii et al 1993).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Different precursor use by the different parts of a plant remains to be explored. Biosynthetic pathways have been very well reviewed at length in several recent works [53,[71][72][73][74][75][76] so we are merely summarizing the key findings and focusing on amelioration in the next section. The synthesis of ascorbate, a precursor of calcium oxalate takes place in the vacuoles of idioblast cells itself.…”
Section: Biosynthesis Of Calcium Oxalatementioning
confidence: 99%
“…The major precursors are ascorbate, glycolate, glyoxylate, oxaloacetate and isocitrate [53,[71][72][73][74][75]. Different precursor use by the different parts of a plant remains to be explored.…”
Section: Biosynthesis Of Calcium Oxalatementioning
confidence: 99%